Analisis Kinerja Ruang Parkir di Pelabuhan Ferry International Batam Center - Emil Adly (Semesta Teknika, 2013)
The growth of motorised vehicle caused the inconvenient to find the parking space in International Ferry Harbour of Batam Center. In this study, the survey was conducted to calculate the number of the motorised vehicle that was going into and out from the harbour especially for two and four-wheeled vehicles on Saturday until Tuesday from 04.00 AM to 04.00 AM WIB. Peak hour for two-wheeled vehicle occurred on Sunday at 12.30-13.29 WIB with numbers of vehicles was 511 vehicles and with the parking lot available is 400 spaces. Thus the parking index for two-wheeled vehicles was 129.2%. Moreover, peak hour for four-wheeled occurred on Sunday at 12.00-12.29 WIB with the number of vehicles was 491 vehicles and with the parking lot available is 380 spaces. Thus the parking index for four-wheeled vehicles was 127.7%. Data on vehicles parking number and parking duration figured that four-wheeled vehicles were the highest number which was 8957 vehicles with the duration of parking less than 1 hour. Furthermore, the highest number of two-wheeled vehicles parking was 3854 vehicles with the duration less than 1 hour. The average number of parking for two-wheeled vehicles and four-wheeled vehicles were 1032 vehicles and 2277 vehicles respectively.